2015
DOI: 10.1007/s00411-015-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of reactive oxygen species by gadolinium oxide nanoparticles under core–inner-shell excitation by proton or monochromatic X-ray irradiation: implication of the contribution from the interatomic de-excitation-mediated nanoradiator effect to dose enhancement

Abstract: Core-inner-valence ionization of high-Z nanoparticle atomic clusters can de-excite electrons through various interatomic de-excitation processes, thereby leading to the ionization of both directly exposed atoms and adjacent neutral atoms within the nanoparticles, and to an enhancement in photon-electron emission, which is termed the nanoradiator effect. To investigate the nanoradiator-mediated dose enhancement in the radio-sensitizing of high-Z nanoparticles, the production of reactive oxygen species (ROS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…This ICD process is a common phenomenon34353637 and a direct source of LEEs that may cause radiation damage either directly or via additional ROS production3839404142. Because the atoms in mid/high-Z nanoparticle species are present in typical van der Waals-bonded cluster environments, electron emissions from proton-irradiated IONs occur via both Auger cascades at the directly ionized iron atoms and ICD paths at nearby neutral iron atoms17. The enhancement of the Shirley background in the electron yield from the ION films demonstrated that more LEEs could potentially be produced from the Fe-Fe ICD-present Fe 3 O 4 nanoparticles via the ICD process than by Fe-Fe ICD-absent FeCl 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ICD process is a common phenomenon34353637 and a direct source of LEEs that may cause radiation damage either directly or via additional ROS production3839404142. Because the atoms in mid/high-Z nanoparticle species are present in typical van der Waals-bonded cluster environments, electron emissions from proton-irradiated IONs occur via both Auger cascades at the directly ionized iron atoms and ICD paths at nearby neutral iron atoms17. The enhancement of the Shirley background in the electron yield from the ION films demonstrated that more LEEs could potentially be produced from the Fe-Fe ICD-present Fe 3 O 4 nanoparticles via the ICD process than by Fe-Fe ICD-absent FeCl 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The CNR effect is defined as the production of burst emissions of fluorescent X-rays and low-energy electrons (LEEs) via Auger cascades and interatomic/intermolecular Coulomb decay (ICD) paths1314 from mid/high-Z nanoparticles under irradiation by a high-energy ion beam15161718.…”
mentioning
confidence: 99%
“…Core-inner-valence ionization of GONs can de-excite electrons via potent Gd-Gd interatomic de-excitation processes. 22 Previous studies have revealed the physical or chemical mechanisms of the dose enhancement effects of GONs, but no biological mechanism for GONs has been determined yet. The radiosensitizing biomechanism of GONs under X-ray irradiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Though effects of some metal-related elements on radio-sensitivity have been reported (33)(34)(35), gadolinium (Gd), a metal-related element, has also been reported to have radiosensitizing effects similar to arsenite. Gd mediates the radiosensitizing effect via ROS that is generated from the metal surface, and the characteristics of the radiosensitivity may be similar to those of arsenite (36,37). A phase I clinical trial of combination therapy of arsenite and radiation for patients with solid tumors has been completed, and the safety of arsenite as a clinical drug was proven (38,39).…”
Section: Radiosensitization By Arsenite In P53-deficient Cells Was mentioning
confidence: 99%